(untitled) (Iraqi Journal of Civil Engineering, 2009)
This research concerns, with studying the proposed of a simulation program, which is related with the process of movement and handling of construction materials on site. to reduce the handling wastes cost. This research deals with all factors affecting construction materials movement on site. Through a proposed program, weakness points of the mentioned factors can be specified and treated either with an applied program or Administrative procedures. Detailed literature survey was performed, detailed field investigation, analysis of collected data, and interviews with selected and well qualified and experienced management personal representing a wide variety of construction firms and companies. The results obtained from the mentioned actions confirmed the research hypothesis. A computer program was prepared, to simulate all construction materials movement stages affecting the movement and handling of construction materials. The proposed program, includes and perform several functions such as , simulation of construction materials management activities, evaluation of the existing status, finding out management solutions and training aspects, that helps in training engineers, possessing little experience in managing construction materials on site. To examine the capability extent of applying the proposed program at the site, the program function applied on tow construction projects and to be examined by experts. The examination was illustrated the program efficiency to reduce movement and handling costs of construction materials. The research recommended the applications of the proposed program to get its benefits and to achieve the research objectives. Further and future researches were proposed, such as expert system to evaluate and develop the performance of construction management in the field of on site materials management.